Les publics d’une stratégie - Arnaud Anciaux (Communication)
The advent of digital computing and the internet has highlighted revealed structural weaknesses in the economics of journalism and increased competition for the attention of audiences. The author conducted a discourse analysis of the institutional and public positions of the Canadian media and communications group Quebecor and also interviewed some of its employees in 2011 and 2012. The aim was to understand how the organization and its staff come to consider their audiences primarily as a set of consumers.